Investigating the variations in the composition and heating of interacting ICMEs - Srivastava, Nandita; Mirtoshev, Zavkiddin; Mishra, Wageesh (Frontiers in Astronomy and Space Sciences, 2023)
Interacting coronal mass ejections (CMEs) have been commonly reported during the STEREO era. With the interaction of CMEs in the heliosphere, it is expected that the participating CMEs will either merge to form a single interplanetary CME (ICME) or will arrive as distinct entities or ICMEs at 1 AU. Previous studies have focused on in situ observations of solar wind, i.e., plasma and magnetic field properties to understand the nature of the CME–CME interaction and its impact. In this study, we examine the observations of composition parameters of those ICMEs that resulted due to the interaction of two CMEs during their propagation between the Sun and the Earth. We report two events of the CME–CME interaction observed in 2012, of which one led to a merged structure after the interaction, as observed at 1 AU. The second interaction event was reported to arrive at L1 as two distinct structures. Our analysis reveals distinct composition signatures in the form of ion charge state enhancements. The results improve our understanding of the signatures of ICMEs and different complex structures formed after the interaction. The study reveals that compression can occur due to the passage of the shock associated with the following CME through the preceding CME and not due to the CME–CME interaction. The results also highlight the importance of the comparison of solar wind proton velocity data with the expected temperature data, in particular, to understand the ICME–ICME interaction processes.